Tackling generic limits for the Neotropical Philonthina with a phylogenetic approach: revision of the genera Linoderus Sharp and Odontolinus Sharp (Coleoptera: Staphylinidae) - Chani Posse, Mariana Raquel (2017)
A systematic revision and a phylogenetic analysis of the Neotropical genera Linoderus Sharp, 1885 and Odontolinus Sharp, 1885 (Staphylininae: Staphylinini: Philonthina) including a broad selection of outgroup taxa is presented. Two valid species are recognized for Linoderus: L. gracilipes Sharp and one new species, L. alajuelensis sp.n. Linoderus navarretei López-García & Méndez-Rojas, 2014 is excluded from the genus Linoderus and synonymized with Belonuchus albovariegatus Bernhauer, 1916. Two valid species are recognized for Odontolinus: O. fasciatus Sharp and a new species, O. campanensis sp.n. Lectotypes are designated for Linoderus gracilipes Sharp, Odontolinus fasciatus Sharp and Belonuchus albovariegatus Bernhauer. The phylogenetic analysis shows both Odontolinus and Linoderus as monophyletic genera that form together with other Central and South American Philonthina a well-supported clade within the Neotropical lineage of this subtribe. The systematic utility of sexually dimorphic characters within the Neotropical lineage is discussed.